The Downy Mildews - Genetics, Molecular Biology and Control
DOI: 10.1007/978-1-4020-8973-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Beta-aminobutyric acid-induced resistance in grapevine against downy mildew: involvement of pterostilbene

Abstract: BABA, a non-protein amino acid, was used to induce resistance in grapevine against downy mildew. BABA-induced resistance was observed in the susceptible cv. Chasselas as well as in the resistant cv. Solaris. Following BABA treatment, sporulation of Plasmopara viticola was strongly reduced and the accumulation of stilbenes increased with time following infection. Induction of trans-piceide, trans-resveratrol and, more importantly, of trans-ɛ-and trans-δ-viniferin and trans-pterostilbene was observed in BABA-pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…coumarins, flavonoids and lignins) derive. The induction of PAL activity preceding an increase in phenolics content has been observed in several BTH-and BABA-mediated induced resistances, as in cucumber-powdery mildew and grapevine-downy mildew interactions (Lin et al 2008;Slaughter et al 2008). However, our study showed no induction of PAL activity in either genotype following treatment (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…coumarins, flavonoids and lignins) derive. The induction of PAL activity preceding an increase in phenolics content has been observed in several BTH-and BABA-mediated induced resistances, as in cucumber-powdery mildew and grapevine-downy mildew interactions (Lin et al 2008;Slaughter et al 2008). However, our study showed no induction of PAL activity in either genotype following treatment (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis inoculated with Hyaloperonospora parasitica, BABA induced callose deposition in sites of penetration, along walls of the penetrated host cells and in the pistil which causes female sterility (Jakab et al 2001;Zimmerli et al 2000); in grape leaves inoculated with Plasmopara viticola, it induces a massive accumulation of lignin (Cohen et al 1999), callose (Hamiduzzaman et al 2005) and pterostilbene (Slaughter et al 2008); in tobacco inoculated with Peronospora tabacina (Cohen 1994) and sunflower inoculated with Puccinia helianthi (Amzalek and Cohen 2007), no microscopic cellular responses were seen.…”
Section: Introductionmentioning
confidence: 97%
“…Among the Oomycetes suppressed by BABA in their respective hosts are Peronospora tabacina in tobacco (Cohen 1994), Hyaloperonospora parasitica in Arabidopsis (Zimmerli et al 2000) and cauliflower (Silue et al 2002), Plasmopara viticola in grape leaves (Cohen et al 1999;Hamiduzzaman et al 2005;Reuveni et al 2001;Slaughter et al 2008), Phytophthora infestans in tomato ) and potato (Cohen 2002), Phytophthora capsici in pepper (Hwang et al 1997), Plasmopara halstedii in sunflower (Tosi et al 1998), and Pseudoperonospora cubensis in cucumber (Walz and Simon 2008). Ascomycetes/Fungi Imperfecti controlled by BABA are Fusarium oxysporum f. sp solani in tomato (Cohen 2002), Botrytis cinerea and Plectosphaerella cucumerina in Arabidopsis (Ton and Mauch-Mani 2004;Zimmerli et al 2001), Monosporascus cannanbolis in melon (Cohen 2002), Alternania alternata in apple fruits (Reuveni et al 2003), Alternania brassisicola in Arabidopsis (Ton and Mauch-Mani 2004), Penicillium digitatum in grapefruit (Porat et al 2003), and Colletotrichum cucumerinum in cucumber (Walz and Simon 2008).…”
Section: Introductionmentioning
confidence: 99%
“…BABA is capable of inducing local and systemic resistance against tobacco mosaic virus (TMV) (Siegrist et al 2000), bacteria (Baysal et al 2005;Wu et al 2009), Oomycetes (Biton et al 2001;Cohen 1994Cohen , 2002Hamiduzzaman et al 2005;Hwang et al 1997;Papavizas and Davey 1963;Reuveni et al 2001;Shailasree et al 2001;Silue et al 2002;Slaughter et al 2008;Tosi et al 1998;Walz and Simon 2009;Zimmerli et al 2000), Ascomycetes and Fungi Imperfecti (Porat et al 2003;Reuveni et al 2003;Ton and Mauch-Mani 2004;Zimmerli et al 2001), Basidiomycetes (Amzalek and Cohen 2007), nematodes (Oka and Cohen 2001;Oka et al 1999) and aphids and chewing insects (Hodge et al 2005(Hodge et al , 2006. In Arabidopsis thaliana BABA is effective against both necrotrophic and biotrophic pathogens, as well as abiotic stresses of drought and salinity (Jakab et al 2001Zimmerli et al 2001).…”
Section: Introductionmentioning
confidence: 97%